Influence of implant scanbody material, position and operator on the accuracy of digital impression for complete-arch: A randomized in vitro trial. Issue 2 (April 2020) - Arcuri, Lorenzo; Pozzi, Alessandro; Lio, Fabrizio; Rompen, Eric; Zechner, Werner; Nardi, Alessandra
Abstract: Purpose: To evaluate the influence of implant scanbody (ISB) material, position and operator on the accuracy of a confocal microscopy intraoral scanning (IOS) for complete-arch implant impression. Methods: An edentulous maxillary model with 6 internal hexagonal connection analogues was scanned with an extraoral optical scanner to achieve a reference file. Three ISBs made of different materials (polyetheretherketone (Pk), titanium (T) and Pk with a titanium base (Pkt)) were scanned with IOS by 3 operators. The resulting 45 test files were aligned to the reference file with a best fit algorithm. Linear (ΔX, ΔY and ΔZ-axis) and angular deviations (ΔANGLE) were assessed. Absolute values of the linear discrepancies were summed up to obtain a global measure of linear absolute error (ΔASS). Influence of ISB material, position and operator was statistically assessed using the mixed general linear model. Results: At multivariate analysis, whenΔASS was considered as response variable, it was identified a significant influence of material ( p  < 0.0001) and position ( p  = 0.0009) while no significant operator effect was detected. When ΔANGLE was considered as response variable, material and position significantly influenced the expected ΔANGLE ( p  = 0.0232 and p  < 0.0001) and no operator effect was identified. Conclusions: The investigated IOS for complete-arch digital impression was influenced by the ISB material with peek reporting the best results on both linear and angular measurements followed by titanium, peek-titanium resulting as the less accurate. Implant angulation affected significantly the linear deviations while implant position the angular deviations. Operator did not show any significant effect on the IOS accuracy.